PENGEMBANGAN INSTRUMEN PENILAIAN KOGNITIF DALAM PEMBELAJARAN TEMATIK TERPADU KELAS 4 SD - Erlin Prasetyo; Wahyudi Wahyudi (Prodi PGMI FTK UIN Ar-Raniry Banda Aceh bekerjasama dengan PW PERGUNU Aceh, 2020)
The purpose of this study is (1) to know how to develop cognitive assessment instruments in the thematic learning of grade 4 elementary school (2) knowingthe valid levelof cognitive assessment instrument development in grade 4 primary school thematic learning based on classical analysis of problem items. (3) know the practicality of the development of cognitive assessment instruments in the thematic learning of grade 4 elementary school based on classical analysis of problem items. This RnD research goes through a preliminary study phase, product development and product trials. The subjects of this study were grade 4 teachers and students of SD Negeri 03 Ampel Boyolali. The results of this study provide the results that (1) how to develop cognitive assessment instruments is to determine a theme, KI, KD, GPA, learning objectives, measuring instruments, grids, question points, validation tests, practicality tests, and determine a final product (2) Item instruments in the form of PG 20 and description consists of 5 questions. Based on validtests conducted by experts, which include integrated thematic material experts got a score of 78 % with the criteria